Adhesion analysis between geopolymer and mineral-asphalt composite - Granatyr, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
The article presents research on the influence of the variable composition of geopolymer concrete on its ability to bond with asphalt concrete. The experimental variables included the proportion of mortar in the geopolymer concrete, the molarity of NaOH in the activator, and the thickness of the geopolymer layer in the road composite. The curing conditions remained constant. Tests were conducted to evaluate interlayer adhesion using the Leutner method, as well as compressive strength, shrinkage, and temperature deformation. The obtained results confirm the interlayer bonding values in each tested case. The interlayer adhesion test was performed according to a three-factor experimental design at three levels of variability. The factors considered were: geopolymer layer thickness (15, 30, 45 mm), molar concentration of NaOH in the activator (8, 10, 12 mol/L), and mortar content in geopolymer concrete (45%, 55%, 65%). All factors significantly influenced interlayer adhesion. The shrinkage of the geopolymer and mineral-asphalt composite was lower than that of geopolymer concrete. Additionally, deformation at both low and high temperatures was lower in the geopolymer and mineral-asphalt composite.